Childhood Middle Ear Tuberculosis–A Rare Case Report - Swain, PK; Mallik, SA; Thapalial, A (Journal of Nepal Paediatric Society, 2009)
Tuberculosis rarely affects the middle ear cleft; the disease is a curiosity and not often considered in the differential diagnosis of otorrhea. The diagnosis is thus made too late, with resulting complications such as irreversible hearing loss and facial nerve paralysis. A case report with review of the literature is presented, emphasizing that tuberculosis should be considered in the differential diagnosis of chronic ear infection in children. In our case direct nosocomial spread of tuebrculous bacilli has been attributed. Key words: Tuberculosis; otitis media, hearing loss & facial paralysis. doi:10.3126/jnps.v27i2.1589 J. Nepal Paediatr. Soc. Vol.27(2) p.93-94